KAJIAN TOKSISITAS LIMBAH BIOSLUDGE YANG BERASAL DARI IPAL INDUSTRI PULP DAN KERTAS DENGAN METODE TOXICITY CHARATERISTIK LEACHING PROCEDURE - Yuzelma Yuzelma; Adrianto Ahmad; Nofrizal Nofrizal (Program Pascasarjana Universitas Riau, 2013)
Pulp and paper industry is one of industry that is relatively much generate solid waste, oneof is the solid waste from the Waste Water Treatment Plant with activated sludge systems,known as biosludge. Biosludge output from the secondary clarifier portion is returned to theprimary clarifier and partly in landfills. Present day this untapped biosludge waste properly,potentially causing pollution as they contain chemicals and hazardous, cause odor and landhoarding unproductive. Present day pulp and paper industries generate solid waste(biosludge) among 3-4 % of the production capacity. In this research has been done the testof Toxcicity Characteristic Leaching Procedure (TCLP). Method TCLP analysis performed isa method of Glass JAR USEPA SW-846 Method 1311. TCLP analysis results for each ofthese metals concentrations in unit mg per liter samples are: arsenic (0.004), barium(0.122), boron (2.66), cadmium (0.011), chromium (0.003), copper (0.025), copper (0.051),mercury (0.0003), selenium (<0.001), silver (<0.001), zinc (0.084). TCLP concentrationswere below the TCLP standards contained in Regulation No. 18 and 85/1999. According tothe delisting hierarchy non hazardous and toxic waste by regulation number 85/1999, wastebiosludge pulp and paper categorized as non hazardous and toxic waste. Althoughcategorized as non hazardous and toxic waste, destruction of the future scenario will come tobe a concern. Given the heavy metals in the environment are not easily degraded and eventends to accumulate in the food chain through biomagnification. It can be harmful to humanhealth, the survival of other creatures and can cause damage to the ecosystem.